The Meta Analysis: Research Variations of Undergraduate Financial Management Students in Indonesia: Meta Analysis: Research Variations of Undergraduate Financial Management Students in Indonesia - Kartika, Kartika; Dheo Rimbano, Indrawati Mara Kesuma, Mulyadi, Ahmad Basri, Amalya Metta Caruna (Adpebi Science Series, 2022)
Undergraduate students in the field of financial management in Indonesia generally do not have variations in conducting research. Thisdue to, pknowledge of general research methodologies is weak, so data and sample collection techniques are difficult to use. Several researchers used the same research title as the previous research.The purpose of this study is to map the variation of research in the field of financial management in Indonesia. This type of research is a qualitative meta-analysis research that uses a data analysis methodology, namely qualitative content analysis techniques. An analytical approach that utilizes a qualitative approach with systematic and analytical qualities is included in the content analysis technique. The method used in this study is content analysis qualitatively referring to the analysis of the material in each implementation procedure. The steps that must be followed are as follows: Selecting five theme categories, analyzing research categories in the field of financial management and selecting 60 research articles. The results of the study indicate that there is still minimal variation in research in the field of financial management. Keywords: Meta Analysis, Financial Management